MEDIA WAYANG SEBAGAI MODEL PEMBELAJARAN BAHASA INDONESIA UNTUK MAHASISWA ASING DI ISI SURAKARTA - Mariani, E.R. Elis Noviati (Acintya, 2016)
Foreign students who study at ISI Surakarta is still plagued with the problem of the use of the Indonesian language. Indonesian official use in teaching and learning in the classroom. Indonesian teachers in the Art Institute of Indonesia Surakarta challenged fortunately find an innovative learning model to address the problems faced by foreign students. Indonesian model of learning through the medium of puppets are considered appropriate to teach the Indonesian language teaching. In addition, the puppet as one of Indonesia’s cultural assets can be used as a form of promotion to introduce Indonesian culture in other countries. Puppet art that is rich in philosophical values and character ofthe characters are very appropriate for learning in the classroom. This study will discuss the alternative learning models with media Indonesian wayang effective for foreign students at ISI Surakarta and introduce philosophical values of what is contained in learning the art of puppet to introduce Indonesian culture. This study includes qualitative research. The results of this study are a Indonesianlearning model that uses media puppets and philosophical values contained in the puppet.Keywords: puppet, media, models, learning, language